Case studies in Economics: Economic policy - Sandford, Cedric T.; Bradbury, M. S. (London: Macmillan, 1977)
The case studies, which illustrate the topics in this volume, consist of detailed examinations of situations, events or developments by means of which economic principles or concepts can be learnt, or significant contemporary happenings in the economy made more meaningful.
Includes bibliographical references.
ne 22/06/2018
Loans
Keywords: Industrial policy; Great Britain